Double-balloon enteroscopy in small bowel diseases: Eight years single-center experience in China. Issue 42 (October 2016) - Chen, Wen-Guo; Shan, Guo-Dong; Zhang, Hong; Yang, Ming; L, Lin; Yue, Min; Chen, Guang-Wu; Gu, Qing; Zhu, Hua-Tuo; Xu, Guo-Qiang; Chen, Li-Hua
Abstract : Abstract: The aim of the study was to evaluate the diagnostic and therapeutic value of double-balloon entoroscopy (DBE) in small bowel diseases (SBDs) in China. A retrospective review of 674 consecutive patients who underwent DBE between January 2007 and November 2015 was conducted. Patients were divided into 3 groups by age, young group (<45 years), middle-aged group (45–65 years), and elderly group (>65 years). Data were collected with regard to demographics, clinical, endoscopic findings, complications, diagnostic yield, and management. A total of 729 DBE procedures were performed successfully in our series. More than 20 types of SBDs were found with the detection rate of 70.9%(517/729). The majority of patients were Crohn's disease (33.4%, 225/674), followed by tumor (18.8%, 127/674) and angioectasia (7.9%, 53/674). Endoscopic treatment was performed in 60 patients in which hemostasis (17, 28.3%) and polypectomy (15, 25%) were the predominant form of intervention used. Adverse events occurred in 6 patients (0.96%, 6/729) including perforation, hemorrhage, aspiration pneumonia. No acute pancreatitis or other major complications occurred. Adenocarcinoma, GIST, and lymphoma were the most common tumor detected, the majority of tumors located in the jejunum (56.7%), The detection rate of angioectasia was also higher in the jejunum (54.7%), 77.8% of Crohn's disease was located in the ileum. The positive rate of DBE in small bowel tumor and Crohn's disease were significantly higher than that of angioectasia ( P <0.05). In young cohort, Crohn's disease (48.1%) was the most commonly diseases followed by tumor (10.4%) and nonspecific enteritis (7.1%). Yet in the elderly group, the majority of patients were tumor (27.6%); angioectasia (21.3%) was also detected frequently. The positive rate of capsule endoscopy was 75.44 %(202/268) which was a little high than DBE (67.9%, 182/268) ( P > 0.05). The obscure gastrointestinal bleeding (OGIB) was the most common indication, and the diagnostic yield was 71.8%. DBE is a useful diagnostic and therapeutic tool with high clinical practice value for the investigation of SBDs. With growing experience of endoscopist, we believe that DBE must be kept in mind as the first-line modality for suspected SBDs.